2019
DOI: 10.1111/imb.12578
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive regulation of detoxification enzymes in Helicoverpa armigera to different host plants

Abstract: Cotton plants produce gossypol as a major secondary metabolite to resist insect herbivores and pathogens. Helicoverpa armigera may employ multigene families of detoxification enzymes to deal with this metabolite. So far, the strength of the transcriptional response to gossypol detoxification in the cotton bollworms remains poorly understood. Here, we investigated the genomewide transcriptional changes that occur in cotton bollworm larvae after one generation feeding on various host plants (cotton, corn, soybea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…P450s, GSTs, UGTs, and CarEs are four insect detoxification enzyme superfamilies that metabolize both phytochemicals and synthetic insecticides. , Cheng et al sequenced the genome of S. litura and investigated the transcriptomic changes after exposure to xanthotoxin, ricin or imidacloprid by using RNA-Seq . The transcriptomic results showed that a fairly large number of detoxification genes were induced when larvae were exposed to xanthotoxin and that a great amount of them are also upregulated by flavone. , This indicates that the metabolic detoxification mechanisms of λ-cyhalothrin tolerance after xanthotoxin ingestion can be inferred from the study of flavone-induced detoxification genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…P450s, GSTs, UGTs, and CarEs are four insect detoxification enzyme superfamilies that metabolize both phytochemicals and synthetic insecticides. , Cheng et al sequenced the genome of S. litura and investigated the transcriptomic changes after exposure to xanthotoxin, ricin or imidacloprid by using RNA-Seq . The transcriptomic results showed that a fairly large number of detoxification genes were induced when larvae were exposed to xanthotoxin and that a great amount of them are also upregulated by flavone. , This indicates that the metabolic detoxification mechanisms of λ-cyhalothrin tolerance after xanthotoxin ingestion can be inferred from the study of flavone-induced detoxification genes.…”
Section: Discussionmentioning
confidence: 99%
“…The induction of metabolic detoxification enzyme systems following exposure to phytochemicals has helped herbivorous insects to detoxify synthetic insecticides . Cytochrome P450 monooxygenases (P450s), uridine diphosphate (UDP)-glycosyltransferases (UGTs), carboxylesterases (CarEs), and glutathione S-transferases (GSTs) are among the detoxification enzymes used by insects in response to both phytochemicals and insecticides. , Phytochemical-inducible detoxification enzymes with “broad-spectrum” substrates can help herbivorous insects tolerate synthetic insecticides. The detoxification genes are induced after exposure to phytochemicals or even constitutively overexpressed after host plant adaptation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that insecticide tolerance in herbivorous insects could arise from utilizing existing detoxification enzymes that evolved to metabolize phytochemicals . The coevolution of herbivorous insects and their host plants has resulted in sophisticated insect detoxification enzyme systems, including cytochrome P450 monooxygenases (P450s), glutathione S -transferases (GSTs), carboxylesterases (CarEs), and uridine diphosphate (UDP)-glycosyltransferases (UGTs). , Up to now, a large number of insect detoxification enzymes that could be induced and metabolize a broad spectrum of phytochemicals, as well as synthetic insecticides, have been identified . For instance, the cotton bollworm, Helicoverpa armigera, maintained on the primary defensive phytochemical gossypol showed elevated tolerance to deltamethrin, and gossypol-induced P450 gene pool contributed to larval tolerance to the pyrethroid insecticide .…”
Section: Introductionmentioning
confidence: 99%
“…The transcriptomic analysis after larvae were allowed to feed on corn, cotton, and tobacco showed that three expanded P450 gene clusters were significantly induced (Fig. 2 B), suggesting a link between the expansion of P450 gene clusters and increased tolerance to plant toxins [ 13 , 23 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%